Effects of the electrode configuration, phase relationship and microstructure on the polarization resistance of La0.3Ba0.7CoO3−δ as cathode material for IT-SOFC - Martinez, Cristian Fabricio (2014)
The polarization resistance of La0.3Ba0.7CoO3−δ (LBC7) as cathode material was studied by impedance spectroscopy measurements in the temperature range of 450 ≤ T ≤ 750 °C, in air, on samples prepared by the solid state reaction (SSR) method and a wet chemical (WC) route, using symmetrical cells with single-layer and graded composition electrodes. While the LBC7 sample prepared by the SSR method and cooled at a rate of 10 °C/min turned out to be single phase with cubic symmetry, the sample prepared by the WC route is a mixture of the cubic phase and the 2H hexagonal phase. The lowest polarization resistance at 600 °C, Rp ∼ 0.06 Ω cm2, was obtained for the graded composition electrodes. Our results suggest that the electrode configuration is a key factor in order to reduce the polarization resistance of the LBC7 electrode material.